Synthesis of Optically Active Maresin 2 and Maresin 2n-3 DPA - Ogawa, Narihito; Amano, Takahito; Kobayashi, Yuichi (Synlett, 2020)
Maresins are among the most potent antiinflammatory lipid metabolites. We report stereoselective syntheses of maresin 2 and maresin 2n-3 DPA. The anti-diol was constructed through epoxide ring opening of an optically active β,γ-epoxy aldehyde, synthesized in situ by Swern oxidation of the corresponding alcohol. Finally, the target compounds were synthesized through a Sonogashira coupling of a C9–C22 iodide and methyl (Z)-oct-4-en-7-ynoate or methyl oct-7-ynoate, respectively.
Keywords: maresins; asymmetric synthesis; trienes; Swern oxidation